Accounting precautionary measures in agriculture through pathway analysis: the case of the Environmental Farm Plan. (27th January 2009) - Summers, Robert J.; Plummer, Ryan; FitzGibbon, John E.
Stewardship programs are an important element of agroecosystems management. These programs are confronted with the difficult challenges of demonstrating their positive impacts on the environment. This paper argues that under the precautionary principle, evaluation of stewardship programs should be aimed at identifying risks mitigated, as opposed to actual changes in environmental conditions. The Ontario Environmental Farm Plan Program is presented as a case study. A pathways model is developed and applied to the case. It demonstrates the types of risks mitigated, a way to account for preventative actions, and insights into how future evaluations based on the precautionary principal can be undertaken.